The de Winter's sign as an ECG equivalent to STEMI - Vukićević Verica; Ilić Andrijana; Mirković Olja; Janković Tamara (Halo 194)
Introduction: In recent years, a popular topic has been the early detection of a unique ECG finding characteristic of proximal occlusion of the left descending artery (LDA) known as the De Winter pattern, which is one of the equivalents of ST-elevation myocardial infarction (STEMI). Objective: This paper's objective is to present a very rare case of early recognition and management of De Winter's ECG pattern in the pre-hospital setting. Case report: An Emergency Medical Team (EMT) was dispatched with the top level of emergency to diagnose and treat a 65-year-old man who fell ill at work. About twenty minutes before the EMT was called, the patient suffered from an onset of sudden, extremely strong chest pain (8/10), propagating into both arms and his back, accompanied by nausea and vomiting. He had a history of hypertension and had an abdominal aneurysm operation in 2017. Upon examination, he was conscious, pale, covered in cold sweat, agitated, and presenting as a seriously ill patient. Auscultatory findings on his lungs and heart were normal. His heart rate and blood pressure were normal (TA 135/80 bilaterally), and his blood oxygen saturation on ambient air was 95%. His ECG tracing showed a normal sinus rhythm of about 70 bpm, a negative T-wave in D3 and aVF leads. The precordial leads showed a reduced R-wave in V2-V4, an upslopping ST depression in V3-V5 with high, symmetrical T-waves in V2-V5. The transition zone was in V5. A prehospital working diagnosis was made: Acute Myocardial Infarction with de Winter T/ST pattern. After placing two IV lines on the patient, administering appropriate medication and establishing continuous monitoring of vital functions, the patient's arrival was announced, and he was transported directly to the catheterisation room. There, the working diagnosis was confirmed by an interventional cardiologist, and a stent was implanted. Conclusion: A timely ECG recording and interpretation in the prehospital setting is vital for managing patients with STEMI. The De Winter's pattern is a rare but significant ECG presentation in patients with LAD occlusion. Failure to recognise the de Winter's sign as a STEMI equivalent can lead to a delay in activating the STEMI network and sometimes be fatal for the patient.